167k views
0 votes
Solve the equation:5x - 1 _____ - 6 = 4x + 2 3

1 Answer

2 votes

First, you can sum 6 on both sides of the equation, like this


\begin{gathered} (5x-1)/(3)-6=4x+2 \\ (5x-1)/(3)-6+6=4x+2+6 \\ (5x-1)/(3)=4x+8 \end{gathered}

Then, you can multiply by 3 on both sides of the equation, like this


\begin{gathered} (5x-1)/(3)\cdot3=(4x+8)\cdot3 \\ 5x-1=12x+24 \end{gathered}

Now, you can sum 1 on both sides of the equation


\begin{gathered} 5x-1=12x+24 \\ 5x-1+1=12x+24+1 \\ 5x=12x+25 \end{gathered}

And now you can subtract 12x from both sides of the equation


\begin{gathered} 5x=12x+25 \\ 5x-12x=12x+25-12x \\ -7x=25 \end{gathered}

Finally, you can divide by -7x on both sides of the equation


\begin{gathered} (-7x)/(-7)=(25)/(-7) \\ x=-(25)/(7) \end{gathered}

User Kyle Heironimus
by
4.9k points